Quantum-dot-based immunochromatographic assay for total IgE in human serum. - Anna N Berlina (Public Library of Science (PLoS), 2013)
To rapidly quantify total immunoglobulin E levels in human serum, we developed a novel quantum-dot-based immunochromatographic assay that employs digital recording of fluorescence. It can detect IgE levels of 5-1000 kU/L, with a coefficient of variation ranging from 2.0 to 9.5%. The assay can be processed in 10 min. The developed assay was tested on 95 serum samples. The correlation coefficient between the IgE values obtained by the proposed assay and those obtained by a commercial ELISA kit was 0.9884. Our assay thus shows promise as a new diagnostic tool for IgE detection.